Análisis integral de los flujos comerciales entre el Perú y China con miras a la firma de un acuerdo de alcance parcial - Gallardo Torres, Carlos (2006)
Trade and its role in economic development have been amongst Peru’s priorities since the country’s economic opening. Along this line, it is easy to understand Peru’s decision to start negotiations to establish trade preference agreements with its main trading partners. This research starts by presenting the scenario for potential trade negotiations between Peru and the People’s Republic of China. The analysis is based on a methodology integrating calculations of trade indicators and the design of tariff item classification and potential identification matrices. Our outcomes’ analysis allows identifying those goods that are actually taking advantage of present trade relations between Peru and China, and other goods that might take further advantage of more open markets once a trade agreement is reached between the two nations. In addition, our research allows preparing a ranking of product classifications taking account of those industries and products where Peru should focus during trade talks with China.